SPATIO-TEMPORAL REGULARITIES OF ATMOSPHERIC MOISTENING COEFFICIENT IN LAKE SEVAN BASIN (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In the work it has been discussed and analysed the moistening regime of the region. Using observed data of deficit and precipitation (1955–2000), we have exposed the number of regularities of spatio-temporal changes. As a result a map of spatial distribution is created.
Keywords: Lake Sevan basin; spatio-temporal regularities; atmospheric moistening coefficient